ASSESSMENT OF THE YOUTH COMPETITIVENESS IN THE LABOR MARKET THROUGH THE TRANSIT OF EDUCATION - Зелінська, Галина Олексіївна; Андрусів, Уляна Ярославівна; Корман, Марія Михайлівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article examines "Transition from education to stable work" (SWTS), which provides an opportunity to analyze the specifics of young people`s transit to the labor market. Research was conducted within the framework of the "Work4Youth" project, which aimed to identify ways of obtaining information about the labor market, namely its youth segment. The main objective of the SWTS was to collect details on the problems, relationships and the situation in which young people aged 15-29 find themselves at the entry and consolidation stage in the labor market. It has been established that in education there is a need to use a management system based on predicting changes, making flexible, balanced decisions, which can provide an innovative model for the development of the management of the educational system and the labor market. An assessment of the youth competitiveness in the labor market was carried out and the regions were studied according to the labor force characteristics. The state of the transition completion from education to employment by a young person has been determined, highlighting the phases of the educational transition and their features. This made it possible to conclude that the quality of human resources in the labor market depends on the educational component. The category of education transit and the educational transition has been defined. The peculiarities of the labor market from the educational phase to a specific moment in time are substantiated. It is proposed to single out the paradoxical phase in the phasic development of education, which is associated with repeated population involvement in updating knowledge and thus replenishing the labor market with a qualitatively trained workforce. It was established that the stabilizing mechanism of the educational system development is the additional administrative (stabilizing) function of educational management, which is connected with ensuring the repeated population involvement in the process of constant knowledge updating and positively reflects on the quality of human resources, and, therefore, on the filling of the national labor market with them. It has been proven that now in education there is a need to use a management system based on the anticipation of changes, making flexible, informed decisions, which can provide an innovative model of the development of the educational system management and the labor market.